Potato residue chips as corn replacement in Angus bulls: Effects on carcass characteristics, meat quality, and serum metabolites - Chang-Xiao Shi; Hui-Li Wang; Ying-Qi Li; Muhammad Aziz-ur-Rahman; Si-Yu Zhang; Jia-Jie Deng; Wen-Xi Zhao; Xing-Yue Yi; Yi-Min Zhang; Yang He; Bing-hai Cao; Hua-Wei Su (Food and Humanity, 2026)

Correction to: Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Correction to: Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Aquaculture-relevant florfenicol exposure causes hepatopancreatic bioaccumulation and metabolic-immune toxicity in the mud crab Scylla paramamosain - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Zhi-Long Chen; Xin-Jian Liu; Zhi-Xun Guo (Environmental Pollution, 2026)

Long-day photoperiod promotes growth of pea (Pisum sativum L.) via auxin biosynthesis and polar transport - Luping Gu; Tao Wan; Wenjie Chen; Guiyu Zhou; Huiyu Zhang; Chang Tan; Lars H. Wegner; Sergey Shabala; Xuewen Li; Jiayou Liu; Yingming Feng; Renfang Shen; et al. (Plant Science, 2026)

Boosting the construction of dual-function photocatalysts: S-scheme heterostructure dual-function catalysts based on Zn-doped ZrO2 and protonated PHI for photocatalytic hydrogen and hydrogen peroxide production - Yan Zhang; Lijiang Wu; Min Liu; Hui Chang; Gang Zhou; Caixiao Li; Yi Li; Deqiang Liu; Zhenliang Luo; Zhejia Zhang; Wenzhen Peng; John Crittenden (Fuel, 2026)

Plasma-engineered chitosan couples red-light bioenergetics to diabetic wound regeneration through programmable microenvironments - Lekshmi Rethi; Hoa Duc Chau; Erlina Febriani; Yan-Ting Chen; Szu-Yu Tung; Pei-Ru Jheng; Yu-Wen Tseng; Rou Li; Min-Lang Tsai; Chun-Chi Chang; Van Khiet Pham; Hieu Trung Nguyen; et al. (Carbohydrate Polymers, 2026)

Identification of Novel Polysaccharide from Myxococcus xanthus and its Function in Developmental Sporulation - Lin Liu; Songchen Jiang; Guirong Yang; Wenming Chang; Jin Lin; Lujun Zhang; Yijia Xu; Xinyu Li; Jie Bai; Lei Zhang; Xianfeng Ye; Yan Huang; et al. (Current Microbiology, 2026)

Seasonal responses of land surface temperature to landscape patterns and multi-objective optimization in urban–rural fringe: a case study of Changqing District of Jinan City, China - Min Wang; Zihan Li; Xiaoyu Wang; Zhongjian Shen; Jinyan Wang; Huanan Wan; Chang’an Zuo; Tianran Wang (Environmental Monitoring and Assessment, 2026)

Food Pattern, Food Selenium and Environmental Stress Regulating the Urinary Selenium in Tibetan Population - Li Wang; Feifei Li; Chang Kong; Hairong Li; Lijuan Gu; Hongqiang Gong; Linsheng Yang; Binggan Wei; Cangjue Nima; Yangzong Deji; Shengcheng Zhao; Min Guo; et al. (Biological Trace Element Research, 2026)

Baicalin alleviates repeated superovulation induced ovarian dysfunction and oocyte impairment by suppressing excessive glycolysis - Lin-Feng Li; Hao Shen; Zhi-Min Qi; Tian Luo; Sheng-Ming Liu; Li-Li Ou; Chang-Long Xu; Yu Liu (Theriogenology, 2026)

Unexpected V-shaped temperature dependence of methane fluxes informing its sources in a megacity of China - Ruilin Zhang; Yibo Huangfu; Bin Yuan; Xiaoxiao Zhang; Xianjun He; Thomas Karl; Yang Ding; Hongjuan Li; Kyung-Eun Min; Ying Xiong; Xiao-Bing Li; Zhe Peng; et al. (Science Bulletin, 2026)

Molecularly functionalized high-Q THz metasurface via q-BIC for selective HbA1c detection - Chang Liu; Min Gao; Zichen Zhang; Junxiao Liu; Ligeng Jin; Xin Tian; Lijun Jiang; Zhongmei Zheng; Chuanyue Li; Jiaming Feng; Xingyu Liao; Zhihang Long; et al. (Chemical Engineering Journal, 2026)

Direct observational evidence of the influence of residual-layer vertical transport on surface nitrate concentrations in a Northern China valley - Jiayun Li; Dantong Chen; Shengtong Lei; Min Zhang; Yiyang Gao; Pengfei Tian; Jinsen Shi; Xin Song; Yi Chang; Zirui Liu; Lei Zhang (Atmospheric Environment, 2026)

Evolution trajectory of auxin response factor across Triticeae species underpin candidate genes for the regulation of salt/alkali stress responsive networks - Canghao Du; Wenboxin Wang; Yemu Chen; Yuxuan Zhang; Bo Wang; Jiayi Zhang; Yixue Zhou; Yiping He; Xiaowen Xing; Mingjie Chen; Junli Chang; Guangxiao Yang; et al. (Plant Cell Reports, 2026)

Stable isotopic niche analysis of the food web in the typical coral reefs of the South China Sea - Chang Sun; Pei Qu; Zhenwei Sun; Jilin Liang; Yuanchao Li; Yulong Zhang; Zongling Wang; Xuelei Zhang; Min Pang (Journal of Oceanology and Limnology, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Time synchronization for LEO navigation signals using space-borne GNSS and ground observations and its impact on LEO-augmented precise positioning - Wenwen Li; Qile Zhao; Chuntao Chang; Zhuo Lei; Min Li; Tengda Huang; Qiangwen Yang (Advances in Space Research, 2026)

Hydrocarbon charging dynamics and its coupling with reservoir densification in a tight sandstone system: Insights from the Jurassic of the Yangxia Sag, Kuqa Depression - Chang-chao Chen; Jun Li; Jinz-hou Wang; Ling Li; Hao-ran Gao; Zheng-lian Pang; Xiu-yan Chen; Min Yang (Applied Geophysics, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Reconceptualizing chorioamnionitis as an immune-mediated inflammatory disorder at the maternal–fetal interface - Tzu-Ming Wang; Chung-Min Shen; Shih-Chang Lin; Wu-Shiun Hsieh; Yi-Li Hung; Jiun-Wen Guo (Inflammation Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Rice-husk biochar-immobilized cadmium-tolerant Pseudomonas aeruginosa S3 for multi-level Cd-contaminated soil remediation - Xinru Luo; Chang Li; Kaiyan Ai; Min Hu; Tao Jiang; Xiancheng Zeng; Liugen Zheng; Chao Wu (Journal of Environmental Chemical Engineering, 2026)

3D printed hierarchically porous Na4Fe3(PO4)2(P2O7) cathodes enabling multiscale Na+ transport for high-areal-capacity sodium-ion batteries - Liang Yang; Fei Shao; Min-Peng Li; Mao-Cheng Liu; Cheng-Gong Chang; Yu-Xia Hu (Chemical Engineering Journal, 2026)

Moisture-driven ionogel neuromorphic sensor for apnea detection and event recognition in wearable patches - Xiu-juan Li; Fa Zhang; Ke-yan Li; Xin Li; Zhen-hui Tao; Ke-xin Wang; Zhen-yu Zhang; Guo Fang; Zi-xin Wang; Jia-yi Xie; Long Zhang; Chang-min Yu; et al. (Chemical Engineering Journal, 2026)

Experimental investigation of contaminant dispersion in vertical drainage pipes induced by toilet flushing - Di Mu; Min Chang; Lu Feng; Ruibin Li; Yan Wu; Naiping Gao (Building and Environment, 2026)

Function and transcription of stoS gene of Xanthomonas campestris pathovar campestris - Kai-Xuan Lin; Hsiao-Ching Chang; Chih-En Li; Chao-Tsai Liao; Yi-Min Hsiao (Antonie van Leeuwenhoek, 2026)

Isolation of new sesquiterpene glycosides from Dendrobium nobile and evaluation of their antitumor activity - Gu Min; Shu-chang Gao; Xiao-li Ma; Xiao-peng Huang; Yi-wei Chen; Xu-liu Shi; Jian-kun Yan; Xu-Hong Duan (Natural Product Research, 2026)

Neurovascular decoupling is associated with altered glymphatic function as assessed by the DTI-ALPS index in patients on dialysis - Wenbo Yang; Lijun Song; Mingan Li; Xiaoyan Bai; Boyan Xu; Min Li; Zhenghan Yang; Tiantian Ma; Yong Gong; Gang Fu; Wenjing Zhao; Jing Zhao; et al. (Brain Imaging and Behavior, 2026)

Design and verification of a microbial consortium with an anchoring-interface enhancement strategy for efficient PAHs degradation in groundwater - Wang Kai Tong; Jiajun Hu; Chaomeng Dai; Jia Jie Zou; Han Tang; Piao Yi Jiang; Min-tian Gao; Jixiang Li; Xihua Wang; Yalei Zhang; Ken-Lin Chang; Kah Hon Leong; et al. (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Structural engineering of C3N5 to intensify the internal dipole field for improved H2O2 activation and tetracycline degradation - Min Li; Chang Liu; Xudong Liu; Zhinan Xie; Chunfang Du; Yiguo Su (Journal of Environmental Chemical Engineering, 2026)

Pomelo peel-graphene aerogel/filter membrane with confocal Raman spectroscopy for rapid separation and identification of microplastics - Zhenqing Dai; Min Chang; Lei He; Yuping Lai; Rijian Mo; Liming Song; Ruikun Sun; Shiqi Jiang; Chengyong Li (Journal of Environmental Chemical Engineering, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Nitrogen doped graphene quantum dots modified a crystalline zinc phosphite based non-enzymatic electrochemical sensor for the ultra-low detection of tyramine - Pi-Chen Wei; Asit Kumar Panda; Yu-Chung Chang; Yi-Rong Li; Todd Hsu; Chih-Min Wang (Food Control, 2026)

Numerical investigation of toilet flushing and exhaust fan operation on aerosol transmission dynamics in building drainage system - Di Mu; Min Chang; Lu Feng; Ruibin Li; Yan Wu; Naiping Gao (Building and Environment, 2026)

Subcellular Structures in Native Hippocampal Synapses Revealed by Cryo-electron Tomography - Chong-Li Tian; Lei Qi; Zhen-Hang Lu; Shuo Liu; Min-Ling Gu; Wen-Lan Huang; Yi-Tong Yan; Yun-Tao Liu; Jing Wu; Peiyi Wang; Z. Hong Zhou; Guo-Qiang Bi; et al. (Neuroscience Bulletin, 2026)

Quantifying fault-controlled radon degassing induced by Pacific Plate subduction in the Miaodao Archipelago, North China - Shujuan Su; Ying Li; Chang Lu; Yanming Yang; Zhaofei Liu; Fengxia Sun; Jun Liu; Qinglin Wang; Zhigang Liu; Hao Sun; Yaowen Zhang; Chunhong Zou; et al. (International Journal of Earth Sciences, 2026)

Dietary bile acids supplementation enhances growth performance, nutrient digestion, hepatic function, rumen fermentation, and modulates quorum sensing in culled ewes - Chang Liu; Lin Li; Min Li; Kehui Ouyang; Mingren Qu; Qinghua Qiu (Animal Feed Science and Technology, 2026)

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Pseudosparassis yunnanensis, gen. et sp. nov. (Sclerotiniaceae, Helotiales, Ascomycota) from Yunnan Province, Southwestern China - Yuan-Hao Ma; Qi Zhao; Li-Mei Huang; Ping Liu; Hong-Mei Chai; Yong-Chang Zhao; Hong-Li Su; Ishika Bera; Wei-Min Chen (Mycological Progress, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Sulfur-doped carbon for enhanced flue gas desulfurization: Synergistic experimental and DFT insights - Jun Li; Xiang Wang; Xiao Zhu; Yuke Li; Min Yan; Yang Ma; Ping Cui; Jingcai Chang; Liqiang Zhang; Tao Wang; Chunyuan Ma; Zhanlong Song (Fuel, 2026)

Targeted degradation of emerging pollutants based on specific recognition and ROS confinement effects of molecularly imprinted cavities - Jun Bo Zhang; Xu Jiang; Chaomeng Dai; Jixiang Li; Jiajun Hu; Min-tian Gao; Xueji You; Hongcheng Zhang; Shunyang Li; Peng Qiu; Zhu Zhu; Xihua Wang; et al. (Chemical Engineering Journal, 2026)

N-coordinated Fe single-atom nanozyme overcomes ATP inhibition for robust tumor catalytic-photothermal therapy - Xiang Chen; Zhikun Huang; Min Xi; Jian Duan; Diankai Wang; Xiaohui Tang; Zhenhua Li; Sijia Xie; Ruixue Liang; Chang Chen; Zheng Deng (Chemical Engineering Journal, 2026)

Patient-derived 3D bioprinted glioblastoma models with defined physicochemical ECM properties for long-term maintenance and CAR-T therapy evaluation - Xiaohui Li; Fei Zhao; Shengqiang Xu; Chunxia Ji; Zupeng Xu; Zhuoxiao Cao; Yexin Gu; Tianyi Feng; Yanbo Wang; Min Tang; Zhengyu Jiang; Yu Yao; et al. (Chemical Engineering Journal, 2026)

Mud crab reovirus infection disrupts the intestinal microbiota and intestinal physiological homeostasis in mud crabs (Scylla paramamosain) - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Xin-Jian Liu; Zhi-Long Chen; Zhi-Xun Guo (Aquaculture, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Copper mediates oxidative stress and immune response in snakehead (Channa argus) through Nrf2 and NF-κB pathway - Xue-qin Wu; Ming-ze Li; Lu Lu; Xiu-mei Chen; Xiao-tian Niu; Yi-di Kong; Gui-qin Wang; Chang-ge Xia; Min Li (Fish & Shellfish Immunology, 2026)

Oxymatrine Alleviates Cerebral Ischemia/Reperfusion Injury By Targeting HDAC1 to Regulate Mitochondria-Related Autophagy and Oxidative Stress - Chang-Sheng Ma; Bo Han; Yu-Xi Liu; Chang-Ku Shi; Dong-Lun Li; Jin-Fen Guo; Min Bai; Shu-Chen Meng; Li-Ying Zhang; Meng-Yuan Duan; Mao-Tao He (Molecular Neurobiology, 2026)
Oxymatrine (OMT), a major alkaloid extracted from Sophora flavescens, has been widely recognized for its anti-inflammatory and anti-cancer properties. However, its precise neuroprotective mechanisms in cerebral ischemia/reperfusion (I/R) injury remain to be fully elucidated. In this study, we combined in vivo and in vitro models to investigate the therapeutic effects of OMT on cerebral I/R injury and glutamate-induced neuronal toxicity during the reperfusion process. In vivo, a mouse middle cerebral artery occlusion (MCAO) model was established to recapitulate I/R injury, whereas glutamate-exposed HT22 hippocampal neurons were utilized as an in vitro model to mimic excitotoxic damage. Bioinformatics analysis, integrated with molecular docking, identified histone deacetylase 1 (HDAC1) as a potential direct target of OMT. Subsequent experimental validation demonstrated that OMT attenuates I/R-induced brain damage by modulating HDAC1-mediated pathways involved in autophagy and oxidative stress regulation. OMT treatment significantly reduced infarct volume and improved neurological function in mice. At the cellular level, OMT suppressed mitochondrial apoptosis and reactive oxygen species (ROS) accumulation, restored mitochondrial membrane integrity, and rebalanced mitochondrial dynamics by downregulating fission-related proteins (Fis1) and upregulating fusion markers (Mfn2). Additionally, OMT inhibited excessive autophagy through modulation of the PINK1/Parkin signaling pathway, as evidenced by decreased expression of LC3-II/I ratio, PINK1, Parkin, and NBR1, along with restored levels of P62.These findings suggest that OMT exerts its neuroprotective effects in cerebral I/R injury by targeting HDAC1, thereby alleviating oxidative stress and excessive autophagy. This study provides new mechanistic insights and supports OMT as a promising therapeutic candidate for ischemic stroke treatment. Graphical Abstract

Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.

Cover Image - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
The cover image is based on the article Macro‐Hybrid and Micro‐Hybrid of Fish by Shaojun Liu et al., https://doi.org/10.1111/raq.70106 . image

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Preparation of walnut shell carbon electrodes with N/P co-doped for capacitive deionization in desalination - Yong Wei; Rongkai Shi; Pu Li; Huangkai Zhao; Yamin Chang; Min Shen (Journal of Environmental Management, 2025)

Fungal mycelial pellet as a biosponge for bacterial immobilization: A novel biocarrier for synergistic adsorption-degradation of PAHs - Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Wang Kai Tong; Hong Cheng Zhang; Min-tian Gao; Yalei Zhang; Zhi Li; Kah Hon Leong; Lang Zhou; Ken-Lin Chang; Swee Pin Yeap (Chemical Engineering Journal, 2025)

Trend in chemical components and sources of PM2.5 and its relationship with ozone in central PRD, China (2018–2023) - Jianfan Yin; Shan Huang; Yunqian Liao; Zihan Li; Bin Yuan; Ming Chang; Weiwen Wang; Xiongzhou Lv; Xihua Li; Shuzhen Su; Xuemei Wang; Min Shao (Atmospheric Environment, 2025)

Correction: Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Soil pH and bacterial diversity synergistically regulate trace element transfer and accumulation in soil-rice systems - Ying Ding; Bao-Min Yao; Hong-Ling Chen; Dong-Li Sun; Zi-Yang Pan; Qing Zeng; Chang-Chun Zhai; Yuan-Kun Liu; Guo-Xin Sun (Soil Ecology Letters, 2025)

Flexible metal-organic frameworks with dual-state emitters (DSEs) Photoluminescence for portable detection and information encryption - Qiao Han; Qingbo An; Xiao Li; Jiaxing Chang; Si Liu; Yining Wang; Zhong-min Su (Analytica Chimica Acta, 2025)

OD-Mind: An ocean drilling expert knowledge query system driven by knowledge graph - Yulong Yang; Weihua Cao; Yupeng Li; Runzhou Chang; Gangcheng Yang; Chao Gan; Min Wu (Ocean Engineering, 2025)

A novel strategy based on mouse organoid biosensor for detecting umami substances and their synergistic effect - Minbo Li; Min Fan; Baifeng Fu; Zhihui Chang; Junjie Yi; Yingqi Xie; Wenwen Ren; Yu Tian; Qiyue Zhao; Shuzhen Cheng; Xianbing Xu; Ming Du (Food Chemistry, 2025)

High-efficient tetracycline removal triggered by Fe-based metal organic framework and sequential reutilization of spent adsorbent - Ting Chang; Yuchen Shang; Shiwen Li; Min Zeng; Jue Liu (Colloids and Surfaces C: Environmental Aspects, 2025)

Heterogeneous oxidation of sulfur dioxide by organic peroxides in 1,3,5-trimethylbenzene-derived secondary organic aerosol: Kinetics and formation of inorganic and organic sulfates - Min Yao; Yong Zhang; Chongxuan Chang; Wenbo Huang; Haiping Luo; Yufeng Jiang; Chenxi Li; Yue Zhao (Atmospheric Environment, 2025)

DNAzyme-driven SDA reaction regulates CRISPR/Cas12a for highly sensitive and selective analysis of underexpressed miRNA - Rufei Cao; Shuji Wang; Qingxi Guo; Hongsheng Xie; Yongxiang Wang; Ting Li; Feifei Chang; Huahua Shi; Shijia Ding; Xun Min; Xiaolei Duan (Analytica Chimica Acta, 2025)

Deep learning-based species identification of gymnosperm xylem: The practice in digital forestry - Chang Zheng; Tuo He; Lichao Jiao; Yang Lu; Shoujia Liu; Tianxiao Li; Yuanyuan Miao; Dejun Feng; Jian Lin; Xian Feng; Zhonghua Huang; Min Yu; et al. (Computers and Electronics in Agriculture, 2025)

Efficient activation of percarbonate by metal-free carbonylated activated carbon for green groundwater remediation: Performance, mechanism, applicability, and environmental implications - Jun Bo Zhang; Yi Yang; Chaomeng Dai; Jixiang Li; Yucang Liang; Jiajun Hu; Min-tian Gao; Xueji You; Xu Jiang; Shunyang Li; Xihua Wang; Zhi Li; et al. (Journal of Hazardous Materials, 2025)

Rapid detection of duck egg ovalbumin (D-OVA) in surimi via fluorescent immunochromatographic assay utilizing shark-derived single-domain antibody - Zhong-Lin Li; Ling-Jing Zhang; Kai-Yuan Cao; Jian-Lian Huang; Chang-Gong Zhang; Le-Chang Sun; Yu-Lei Chen; Min-Jie Cao (Food Chemistry, 2025)

Application potential of submicron-sized bamboo cellulose as natural Pickering emulsion stabilizers: Structural properties and stabilization mechanisms - Chen-long Hou; Hao-tian Wei; Chang Liu; Hui-min Yang; Li-Chun Chen; Jian-ping Xu; Lu-yao Wang; Xiu-hua Rao; Jian-jun Huang; Qing Ge (Food Chemistry, 2025)

Engineered clay-alginate composites for tetracycline removal: Mechanistic insights and sustainable processing - Hualing Zhao; M.M.M. Ahmed; Yating Yang; Yuhan Li; Yaqi Wen; Zhaohui Li; Po-Hsiang Chang; Yu-Min Tzou (Environmental Research, 2025)

Associations of urinary biomarkers of exposure to drinking-water disinfection by-products with haematological parameters and systemic inflammation indices among women undergoing assisted reproductive technology treatment - A-Xue Liu; Yu Miao; Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Jia-Yue Zeng; Yang-Juan Li; Wen-Qing Lu; Chang-Jiang Liu; Qiang Zeng (Environmental Pollution, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Seasonal growth and biomass production of cold-tolerant Napier Grass line L2201 - Swee-Suak Ko; Tzu-Rung Li; Jo-Chi Hung; Hsien-Chang Kuo; Min-Jeng Li; Jeng-Bin Lin; Ping-Han Chung; Lin-Hsiang Lee; Yueh-Hua Lin; Hong-Ping Lin; Charles C.-K Chou; Kuo-Chen Yeh (Biomass and Bioenergy, 2025)

Generation of donor-derived spermatozoa by cross-subfamily transplantation of purple loach (Leptobotia taeniops) spermatogonia into triploid loach (Misgurnus anguillicaudatus) - Yihui Mei; Min Guan; Yuxuan Zheng; Yunbang Zhang; Qingshan Li; Yasmeen Gul; Yankun Guo; Yuxing Jiang; Wenqi Chang; Yuwei Huang; Nan Zhang; Jian Gao; et al. (Fish Physiology and Biochemistry, 2025)

Tailoring lignocellulose-derived biochar for peroxymonosulfate-based catalytic environments: Optimizing active sites, revealing activation mechanisms, and advancing groundwater remediation applications - Jun Bo Zhang; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Yeap Swee Pin; Kah Hon Leong; Ken-Lin Chang; Xing Song Xu; Xu Jiang (Journal of Hazardous Materials, 2025)

DCNet: Full waveform inversion with difference convolution - Li-Sha Fu; Chang-Yang Hu; Leting Tan; Huawei Liao; Qiang Zhang; Fan Min (Journal of Applied Geophysics, 2025)

A novel phage LTH02 for shiga toxin-producing Escherichia coli: Biological characteristics, whole genomic analysis, and preliminary application in food - Mingwei Ma; Zhenhuan He; Xiaonan Yang; Yinghao He; Leiqian Huang; Chang Liu; Jing Mu; Lei Lei; Gonghe Li; Wende Wu; Min Zheng; Mingxian Shi; et al. (Food Bioscience, 2025)

The Impact of Tidal Effects on the Deformation and Internal Forces of Coastal Deep Excavations - Run-min Hao; Yan-kai Wu; Chang-hui Gao; Hui Li; Chun-ying Xia; Yuan-zhi Tan (Applied Geophysics, 2025)

Inactivation performance of virus and bacterium in water by dielectric barrier discharge coupled with pulse corona discharge plasma - Pengcheng Yan; Rong Zhang; Min Zhang; Chang Wen; Yuxin Cheng; Zhenghui Liu; Guangzhou Qu; Ronghua Li; Tiecheng Wang; Fei Ling (Journal of Water Process Engineering, 2025)

Environmental high-risk efflux pumps mediate concurrent enhancement of resistance and virulence in reclaimed water from urban wastewater treatment plants - Shanqi Shen; Zhong He; Siya Zhao; Zezhang Zhu; Xinyi Wang; Yechao Tian; Yuze Han; Min Hu; Chang Lu; Aimin Li (Journal of Hazardous Materials, 2025)

Prim-O-glucosylcimifugin-loaded nanodrug hydrogel alleviates periodontitis and colitis via modulating macrophage polarization and microbiota balance - Chengye Ding; Xinjia Cai; He Zhang; Yixin Ma; Liyuan Chen; Xiaolan Wu; Min Yu; Chang Li; Hangbo Liu; Shiying Zhang; Xinmeng Shi; Ting Zhang; et al. (Chemical Engineering Journal, 2025)

Investigating the fine structures of ginkgo starch during kernel development and their correlations with thermal properties - Yan Lu; Lian Zhou; Cai-Yun Zhang; Yan Qi; Xiao-Min Zhang; Zhang Pan; Hong-Jia Zhang; Yu-Ping Ling; Qing Liu; Chang-Quan Zhang; Li Wang (Food Chemistry, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Retinal vessel diameter reflects altered resting-state fMRI connectivity and cognitive performance: A community-based study - Yan Min; Chang Liu; Yanli Zhang; Yuesong Pan; Tao Liu; Hongyu Zhou; Zixiao Li; Yongjun Wang (GeroScience, 2025)

Genome-wide identification, expression analysis and transcriptional regulation of major histocompatibility complex class I genes in mandarin fish Siniperca chuatsi - Jing Hou; Min Chang Li; Lu Qi; Wei Hao; Lan Hao Liu; Zhen Gan; Bei Huang; Wen Shu Huang; Li Wang; Li Li; Shan Nan Chen; Pin Nie (Aquaculture, 2025)

Synergistic effects of matrix metalloproteinases on the degradation of collagen in abalone (Haliotis discus hannai) - Yu-Lei Chen; Le-Le Su; Hua Liu; Tian-Bo Zhang; Guiling Li; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2025)

Orthogonal DNA self-assembly technology enables rapid and accurate analysis of circulating tumor cells in breast cancer - Min Li; Runchi Zhang; Xiaozhi Huang; Meng Jian; Haipeng Qi; Xiaolong Chen; Jie Deng; Wen Chen; Chang Feng; Qiongzhu Dong; Bin Su (Analytica Chimica Acta, 2025)

Molecular networking reveals indole diterpenoids from the marine-derived fungus Penicillium sp. N4-3 - Min Chen; Bao-Cong Hao; Xia-Hao Zhu; Li-Kui Zhang; Yao-Yao Zheng; Xiao-Jian Zhou; Till F. Schäberle; Li Shen; Chang-Yun Wang; Yang Liu (Marine Life Science & Technology, 2025)
MS/MS-based molecular networking is an effective strategy to rapidly dereplicate known compounds and to guide the discovery process for new and novel natural products. In the present study, the chemical diversity of indole diterpenoids from the marine-derived fungus Penicillium sp. N4-3 was investigated using molecular networking techniques. Guided by this information, targeted isolation resulted in two new indole diterpenoids shearinines R and S ( 1 , 2 ) and an oxidative artifact shearinine T ( 3 ), together with the verification of two known analogs ( 4 , 5 ). Furthermore, five indole diterpenoids ( 6 − 10 ), including three putatively new ones, shearinines U−W ( 6 , 9 , 10 ), were predicted from the molecular ion cluster by the combination of GNPS molecular networking and manual analysis of MS/MS fragmentation clusters. Shearinines T ( 3 ) and W ( 10 ) are characterized by an oxidative cleavage of the C-2–C-18 double bond. Feature fragment ions of these shearinines revealed two type of dominant ions related to the indole moiety and the breaking of C-9 side chain or Ring I. Compound 1 showed antibacterial activities against a panel of pathogenic bacteria with IC 50 values ranging from 6.34 to 47.96 μg/mL and inhibited the growth of the human hepatic (HepG2) and gastric (SGC-7901) cancer cells lines with IC 50 values of 6.27 and 19.16 μg/mL, respectively.

Repeated measurements of urinary bisphenol A and its analogues in relation to sperm DNA damage - Yang-Juan Li; A-Xue Liu; Jia-Yue Zeng; Yu Miao; Min Zhang; Xiao-Ying Liu; Wu Yang; Ru-Cheng Li; Jin-Qin Zhu; Chang-Jiang Liu; Qiang Zeng (Journal of Hazardous Materials, 2025)

Interfacial structure design enables rapid reaction kinetics for high-voltage NCM 613 cathodes - Yuan Xiao; Rong Gu; Tingting Zheng; Bowen Chang; Qiaoxia Li; Shuaiqi Gong; Xin Wei; Qunjie Xu; Yulin Min (Chemical Engineering Journal, 2025)

Transcriptomic and Metabolomic Analyses Reveal Response Mechanisms of Sinonovacula Constricta to Saline-Alkalinity Stresses - Min Yang; Yuting Han; Yujie Chang; Chengbo Li; Donghong Niu (Marine Biotechnology, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Discrete fracture network model benchmarks developed and applied in a DECOVALEX-2023 repository performance assessment study - Paul E. Mariner; Rosie C. Leone; Emily R. Stein; Jeffrey D. Hyman; Jan Thiedau; Zhenze Li; Son Nguyen; Yong-Min Kim; Jung-Woo Kim; Chieh-Chun Chang; Scott A. Briggs; Mark Gobien; et al. (Geomechanics for Energy and the Environment, 2025)

Comparison of performance assessment models and methods in crystalline rock: Task F1 DECOVALEX-2023 - Rosie C. Leone; Paul E. Mariner; Emily R. Stein; Jeffrey D. Hyman; Jan Thiedau; Carlos R. Guevara Morel; Zhenze Li; Son Nguyen; Yong-Min Kim; Jung-Woo Kim; Chieh-Chun Chang; Ondrej Mikláš; et al. (Geomechanics for Energy and the Environment, 2025)

A method for improving the gelation properties and 3D printing performance of reduced-sodium chicken breast paste: The addition of tiger nut protein, transglutaminase, and calcium chloride - Ya-Li Yu; Ning Huo; Min Guo; Yi-Tao Fan; Xin-Yu Jiang; Yan-jiao Chang; Feng Gao (Food Hydrocolloids, 2025)

Protection of glutamine: The NF-κB/MLCK/MLC2 signaling pathway mediated by tight junction affects oxidative stress, inflammation and apoptosis in snakehead (Channa argus) - Xue-qin Wu; Ji-wu Wan; Zhi-nan Yang; Hong-jian Liu; Yue Chang; Si-bo Peng; Xiao-tian Niu; Yi-di Kong; Min Li; Xiu-mei Chen; Gui-qin Wang (Fish & Shellfish Immunology, 2025)

Performance and mechanism of the controllable gaseous ClO2 generation with modified sepiolite-based porous materials - Nana Chang; Wanting Li; Mingming Fei; Min Tie; Hao Ling; Yunlei Zhao; Xiayi Hu (Applied Clay Science, 2025)

Dynamics and energetics of semidiurnal internal tides in the Weddell-Scotia Confluence - Wenjia Min; Qun Li; Zhiliang Liu; Bo Zhao; Yue Ma; Hang Chang; Weidong Wang (Acta Oceanologica Sinica, 2025)

A Turn-On Ratiometric Fluorescence Probe Based on Dye@MOFs for Visual Detection of AFB1 with Paper Sensor Assisted by Smartphone - Zhangmin Li; Zuopeng Li; Qianyi Li; Min Wang; Chang-qing Miao; Yajia Liu; Sanbing Zhang (Journal of Fluorescence, 2025)

Using machine learning to predict selenium content in crops: Implications for soil health and agricultural land utilization in longevity regions - Liyue Zhang; Tao Yu; Guodong Zheng; Qifeng Tang; Min Peng; Chang Li; Qingye Hou; Zhongfang Yang (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

When digital disadvantage meets transport disadvantage: The association between smartphone-based mobility services and perceived transport disadvantage among the elderly - Enyu Chang; Min Zhang; Zhixuan Li; Yuchen Hu (Journal of Transport Geography, 2025)

The diversity and disparity of mineral elements in global kiwifruits - Dawei LI; Yan Min; Chang Cheng; Xiaoying Liu; Xiaodong Xie; Gudeta Chalchisa; Cheng Peng; Quan Jiang; Naidong Xiao; Jianbo Cai; Caihong Zhong (Food Research International, 2025)

Encapsulation of rose anthocyanins with β-cyclodextrin for enhanced stability: Preparation, characterization, and its application in rose juice - Yu Xiong; Min Chang; Zhen-Wei Shi; Yuan-Yuan Li; Si-Yang An; Di-Feng Ren (Food Bioscience, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Impact of different continuous fertilizations on the antibiotic resistome associated with a subtropical triple-cropping system over one decade - Jin Zheng; Ya-Ying Li; Yu-Sheng Lu; Dan Wang; Chong Liu; Huan-Long Peng; Chao-Hong Shi; Kai-Zhi Xie; Kun Zhang; Li-Li Sun; Chang-Min Zhou; Wen-Jie Gu (Environmental Pollution, 2025)

Influence of the main controlling factors on the tangential restitution coefficient of rockfall impact - Zhong-Min Ji; Ting-Hui Wang; Jie Wu; Fa-Quan Wu; Zhen-Hua Li; Dong-Po Wang; Yi-Ju Tang; Chang-Le Zhao; Qing-He Niu (Engineering Geology, 2025)

H-NS represses fliD transcription for lateral flagellar filament cap in Vibrio parahaemolyticus - Kui Liu; Min Chen; Jingyang Chang; Jing Yang; Daqing Wang; Xuefeng Ding; Ming Yang; Yiquan Zhang; Renfei Lu; Li Chen (Archives of Microbiology, 2025)

Phthalate exposures, blood coagulation function, and assisted reproductive technology outcomes: Results from the TREE cohort study - Chong Liu; Chang-Jiang Liu; Wen-Qu Tian; Wen Yao; Yu Miao; Min Zhang; Xiao-Qiong Yuan; Yan-Ling Deng; Wen-Qing Lu; Yu-Feng Li; Qiang Zeng (Environmental Research, 2025)

Cs-Doped BCCF perovskite with enhanced surface proton acid sites for high-performance R-PCECs - Yang Gao; Kechen Liu; Xuan Zhang; Qi Li; Yinling Chang; Min Fu; Zetian Tao (Chemical Engineering Journal, 2025)

Organic matter determines the exchange of nutrients at sediment-water interface in coastal bays - Jiasen Zhong; Ehui Tan; Chunwei Fu; Guiyi Ma; Yongkai Chang; Zhixiong Huang; Jingchao Yin; Fengying Li; Jianzhong Su; Min Xu; Zhenzhen Zheng; Jian’an Liu; et al. (Acta Oceanologica Sinica, 2025)

The Research Advances in Distant Hybridization and Gynogenesis in Fish - Qizhi Liu; Shi Wang; Chenchen Tang; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Kaikun Luo; Chang Wu; Fangzhou Hu; Yude Wang; Qingfeng Liu; et al. (Reviews in Aquaculture, 2025)
Distant hybridization and gynogenesis are two prevalent breeding techniques for fishes. Drawing from the research achievements of our team and the existing literature, we summarize the reproductive traits and genetic features of fishes derived from distant hybridizations and gynogenesis, and we deduce the fundamental mechanisms of these two methods and compare them, discerning their common and different characteristics. Both distant hybridization and gynogenesis techniques can alter genotypes and phenotypes, thus establishing them as significant breeding methods. Additionally, the genetic principles and the basic biological characteristics of distant hybridization and gynogenesis in fish have been inferred. We propose the concepts of macro‐hybrid and micro‐hybrid based on extensive experimental findings from fish distant hybridizations and gynogenesis. The term “macro‐hybrid” refers to offspring from distant hybridization that possess two distinct subgenomes, each inherited from one of the two parental species, such as allodiploid and allotetraploid lineages. The concept of “micro‐hybrid” refers to offspring, including autodiploid and autotetraploid lineages, as well as those resulting from artificial gynogenesis, whose genome almost originates solely from the maternal parent but in which certain DNA fragments derived from the paternal parent insert. Distant hybridization and gynogenesis are vital techniques in fish genetics, breeding, and evolution. We highlight the prospective paths for research and application of distant hybridization and gynogenesis in fishes.

China-specific unit process dataset for lithium-ion batteries - Xi Tian; Haoyu Li; Fei Peng; Yibing Wang; Kaiwen Xiong; Rongjian Zhao; Min Liao; Yaodan Zhang; Bingqian Zhang; Jinliang Xie; Huimin Chang; Xin Sun; et al. (Resources, Conservation and Recycling, 2024)

Nature-inspired ultrathin wood-based interfacial solar steam generators for high-efficiency water purification - Min Li; Yating Sun; Yuzhang Lei; Gonggang Liu; Heng Jiang; Yong Wang; Shanshan Chang; Xianjun Li; Jinbo Hu (Desalination, 2024)

Photothermal enhanced antibacterial chitosan-based polydopamine composite hydrogel for hemostasis and burn wound repairing - Liming Chang; Yanai Chen; Min Zhou; Yuanwei Gao; Yong Wang; Wenjuan Li; Zhe Cui; Chengyan Zhou; Yingna He; Jianglei Qin (Carbohydrate Polymers, 2024)

Further geochronological constraints on the Xiuyan impact crater in northeast China - Zeyang Zhu; Chang Huang; Jing Wu; Yawei Li; Zhihao Sun; Min Zhang; Bin Zhang; Sheng-Hua Li; Jiaqi Liu (Frontiers of Earth Science, 2024)

Transcriptome analysis of Scylla paramamosain hepatopancreas response to mud crab dicistrovirus-1 infection - Min-Ze Liao; Chang-Hong Cheng; Gui-Ying Li; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Jian-Jun Jiang; Juan Feng; Zhi-Xun Guo (Fish & Shellfish Immunology, 2024)

Metagenomic analysis unveiled the response of microbial community and antimicrobial resistome in natural water body to duck farm sewage - Chang Fang; Kai-di Liu; Feng-jie Tian; Jin-ying Li; Si-jie Li; Rong-min Zhang; Jian Sun; Liang-xing Fang; Hao Ren; Min-ge Wang; Xiao-ping Liao (Environmental Pollution, 2024)

Quenching-induced amorphisation and configuration transformation for the enhanced electrochemical performance of poly(vinylidene fluoride-hexafluoropropylene)-based solid electrolytes - Yaguang Zhang; Jianxun Zou; Ruirui Chang; Zixuan Min; Shuping Dong; Zhijia Tang; Xuandu Li; Jingjing Tang; Juan Yang; Xiangyang Zhou (Chemical Engineering Journal, 2024)

Efficient ethidium bromide removal using sodium alginate/graphene oxide composite beads: Insights into adsorption mechanisms and performance - Po-Hsiang Chang; Yating Yang; Yaqi Wen; M.M.M. Ahmed; Jou-Chieh Chang; Ting-Yu Chang; Yu-Min Tzou; Zhaohui Li; Ahmed I. Osman (Chemical Engineering Journal, 2024)

In situ surface-enhanced Raman spectroscopy for the detection of nanoplastics: A novel approach inspired by the aging of nanoplastics - Xiaoxin Huang; Jinchan Huang; Meilin Lu; Yu Liu; Guangzheng Jiang; Min Chang; Wenhui Xu; Zhenqing Dai; Chunxia Zhou; Pengzhi Hong; Chengyong Li (Science of The Total Environment, 2024)

Mechanical-vibration-driven piezocatalytic degradation of organic pollutants over microcrystalline SnSe with selenium vacancies - Yue Liu; Huan-Yan Xu; Bo Li; Mao-Chang Cao; Li-Guo Jin; Lian-Wei Shan; Li-Min Dong (Chemical Engineering Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

An acridone based fluorescent dye for lipid droplet tracking and cancer diagnosis - Dat Thanh Dinh; Chia-Ying Li; Min-Wei Wu; Chia-Feng Hsieh; Xuan-Yu Chen; Cheng-Chung Chang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Local microenvironment modulation of zirconium-porphyrinic frameworks for CO2 reduction - Xue Zhao; Chang-Yan Zhu; Heng Rao; Dong-Ying Du; Min Zhang; Ping She; Li Li; Jun-Sheng Qin (Chemical Engineering Journal, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Failure Mechanism and Active Support of Large-Span Tunnel with Unstable Rock Blocks: A Case Study - Wen-xu Li; Zhi-chao Xue; Le-min Liu; Shuo Zhang; Fu-yong Zhang; Wei-teng Li; Xin-jie Man; Xing Shao; Ming-fa Wang; Chang-an Zhang (Geotechnical and Geological Engineering, 2024)

Characterization and Genomic Analysis of Affinirhizobium gouqiense sp. nov. Isolated from Seawater of Gouqi Island Located in the East China Sea and Reclassification of Rhizobium lemnae to the Genus Affinirhizobium as Affinirhizobium lemnae comb. nov. - Min He; Gen Chen; Ke-Jing Li; Xing-Xing Tang; Xiao-Xiao Liu; Chang-Bin Ren; Hou-Hong Liu; Hai Luo; Sanjit Chandra Debnath; Pin-Mei Wang; Hai-Xin Chen; Dao-Qiong Zheng (Current Microbiology, 2024)

Experimental and numerical study on seismic performance of assembled platform canopy with mortise-tenon joints - Yu-zhen Chang; Jiu-yi Kuang; Chong Bai; Yu-jun Cai; Dan-ning Wang; Yuan Wang; Li-min Tian (Soil Dynamics and Earthquake Engineering, 2024)

Deep learning-based geological map generation using geological routes - Chaoling Li; Fengdan Li; Chang Liu; Zhen Tang; Si Fu; Min Lin; Xia Lv; Shuang Liu; Yuanyuan Liu (Remote Sensing of Environment, 2024)

Wildfire-vegetation-climate-human interactions in the central Taiwan region during 17.3–2.0 cal kyr BP, inferred from sediments of Toushe Basin - Abdur Rahman; Yuan-Pin Chang; Hong-Chun Li; Ling-Ho Chung; Yu-Min Chou; Liang-Chi Wang (Quaternary Science Reviews, 2024)

Targeted isolation of prenylated indole alkaloids from the marine-derived fungus Penicillium janthinellum HK1‑6 using molecular networking - Bao-Cong Hao; Yao-Yao Zheng; Zhong-Hui Li; Cai-Juan Zheng; Chang-Yun Wang; Min Chen (Natural Product Research, 2024)

High sensitivity in quantitative analysis of mixed-size polystyrene micro/nanoplastics in one step - Wenhui Xu; Zhenqing Dai; Xiaoxin Huang; Guangzheng Jiang; Min Chang; Chenying Wang; Tingting Lai; Huanming Liu; Ruikun Sun; Chengyong Li (Science of The Total Environment, 2024)

Multiple non-covalent interactions for mechanically robust and electrically detachable liquid-free poly(ionic liquids) ionoadhesives - Jin Liu; Siyu Gan; Daixuan Yang; Qilin Yue; Shijie Sun; Min Wu; Xiuyun Li; Guanjun Chang; Yong Wei (Chemical Engineering Journal, 2024)

Exploring the chemical diversity of sesquiterpenes from the rarely studied south China sea soft coral Sinularia tumulosa assisted by molecular networking strategy - Sheng-Hui Zhu; Yuan-Min Chang; Song-Wei Li; Ming-Zhi Su; Li-Gong Yao; Lin-Fu Liang; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

Analysing the influence of surface greening on soil conservation in China using satellite remote sensing - Jiaqi Yao; Jing Li; Yongqiang Cao; Min Chen; Chenyue Zhang; Fan Mo; Guodong Jia; Huanyu Chang; Jianjun Wu (Journal of Hydrology, 2024)

Enhancing thermoelectric performance of solution-processed polycrystalline SnSe with PbSe nanocrystals - Yu Liu; Seungho Lee; Christine Fiedler; Maria Chiara Spadaro; Cheng Chang; Mingquan Li; Min Hong; Jordi Arbiol; Maria Ibáñez (Chemical Engineering Journal, 2024)

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Fucoidan-coated cotton dressing functionalized with biomolecules capped silver nanoparticles (LB-Ag NPs–FN–OCG) for rapid healing therapy of infected wounds - Kandasamy Saravanakumar; Zijun Li; Yebon Kim; SeonJu Park; Kim Keon; Chang-Min Lee; Ginnae Ahn; Namki Cho (Environmental Research, 2024)

Determination of the Elemental Iodine in Human Breast Milk by Inductively Coupled Plasma mass Spectrometry - Chun-Jui Huang; Jia-Zhen Li; Chii-Min Hwu; Harn-Shen Chen; Chang-Ching Yeh; Fan-Fen Wang; Chen-Chang Yang (Biological Trace Element Research, 2024)

Identification of sex locus and a male-specific marker in blunt-snout bream (Megalobrama amblycephala) using a whole genome resequencing method - Ming Wen; Siyu Wang; Chunchun Zhu; Yuxin Zhang; Zheng Liu; Chang Wu; Shi Wang; Yude Wang; Li Ren; Min Tao; QinBo Qin; Chun Zhang; et al. (Aquaculture, 2024)

Integrating the confinement effect and bimetallic cycles in a hierarchical Co3O4@Co3O4/Fe3O4 yolk-shell nanoreactor for peroxymonosulfate activation enhancement - Bo Li; Huan-Yan Xu; Gu-Hao-Nan Chi; Li-Min Dong; Lian-Wei Shan; Li-Guo Jin; Yan-Li Zhuang; Mao-Chang Cao; Xiu-Lan He; Shu-Yan Qi (Chemical Engineering Journal, 2024)

Recycling Efficiencies in Japan’s Administrative Regions: Findings from Network Data Envelopment Analysis - Jin-Li Hu; Satoshi Honma; Tzu-Min Chang (Circular Economy and Sustainability, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Differences in the gelation, digestibility and release of antioxidant peptides of egg white/yolk in boiled eggs - Min Zhu; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Engineered antler stem cells derived exosomes potentiate anti-tumor efficacy of immune checkpoint inhibitor by reprogramming immunosuppressive tumor microenvironment - Min Yang; Li Pu; Shuiyue Yang; Ze Chen; Jia Guo; Ying Liu; Shuzhuo Chang; Yinghua Peng (Chemical Engineering Journal, 2024)

LEO augmented precise point positioning using real observations from two CENTISPACE™ experimental satellites - Wenwen Li; Qiangwen Yang; Xiaodong Du; Min Li; Qile Zhao; Long Yang; Yanan Qin; Chuntao Chang; Yubin Wang; Geer Qin (GPS Solutions, 2024)

First report of Fusarium sacchari causing root rot of tobacco (Nicotiana tabacum L.) in China - Rui Qiu; Caihong Li; Xiaojie Li; Yingying Zhang; Chang Liu; Chenjun Li; Yuguo Chen; Jingke Bai; Min Xu; Ruifang Song; Shujun Li (Crop Protection, 2023)

Energy-efficient fluorine-free electro-refining of crude lead in a green methanesulfonic acid system - You-gang Li; Cong Chang; Jun-jie Qu; Chang-liu Xiang; Tao Luo; Shan-shan Liu; Shuai Li; Sheng-hai Yang; Heng-hui Wang; Xiao-bo Min; Chang-hong Wang; Yong-ming Chen (Journal of Environmental Chemical Engineering, 2023)

Effects of rotation and Bacillus on the changes of continuous cropping soil fungal communities in American ginseng - Fengan Jia; Fan Chang; Min Guan; Qingan Jia; Yan Sun; Zhi Li (World Journal of Microbiology and Biotechnology, 2023)
The continuous cropping obstacle is the main factor in leading to difficulty in American ginseng replanting. The dormant microbiota in the soil may be the cause of American ginseng disease and eventually caused continuous cropping obstacles, but there are few studies on the dynamic changes of soil microenvironment after American ginseng planting. In this study, we tracked short-term variation in physicochemical properties, enzyme activities, and fungal communities over time-series in soils with continuous cropping obstacle under crop rotation and probiotic Bacillus treatments. Furthermore, we examined the relationships between the important fungal compositions and the soil properties. The results showed that sucrase, cellulase, urease and acid phosphatase activities were significantly increased, while catalase and dehydrogenase were decreased with treatments time. Rotation treatment significantly affected the diversity, dissimilarity degree and species distribution of soil fungal community with continuous cropping obstacle over a short-term. Moreover, beneficial fungal biomarkers such as Cladorrhinum , Oidiodendron , and Mariannaea were accumulated at 48 h under rotation treatments. Almost all fungal biomarkers were negatively correlated with hydrolases and positively correlated with oxidoreductases and acid phosphatase under crop rotation treatments. This study suggested that compared to probiotic Bacillus , crop rotation can significantly affect soil fungal community structure, especially the enrichment of specific potentially beneficial fungal species. Our findings provide a scientific basis for understanding the dynamic changes of fungal communities and soil properties with continuous cropping obstacle of American ginseng in initial stage of soil improvement.

Overcoming the fluorescent interference during Raman spectroscopy detection of microplastics - Yu Liu; Jiale Hu; Liqian Lin; Bing Yang; Minhua Huang; Min Chang; Xiaoxin Huang; Zhenqing Dai; Shengli Sun; Lei Ren; Chengyong Li (Science of The Total Environment, 2023)

Zebrafish nos2a benefits bacterial proliferation via suppressing ROS and inducing NO production to impair the expressions of inflammatory cytokines and antibacterial genes - Si Yao Zheng; Xinbin Shao; Zhitao Qi; Maocang Yan; Min Hui Tao; Xiao Man Wu; Lining Zhang; Jianzhong Ma; An Li; Ming Xian Chang (Fish & Shellfish Immunology, 2023)

Significant roles of aged dust aerosols on rapid nitrate formation under dry conditions in a semi-arid city - Jiayun Li; Naiyue Zhang; Pengfei Tian; Min Zhang; Jinsen Shi; Yi Chang; Lei Zhang; Zirui Liu; Yuesi Wang (Environmental Pollution, 2023)

The effect of chronic intermittent hypobaric hypoxia improving liver damage in metabolic syndrome rats through ferritinophagy - Fang Cui; Haichao Mi; Ruotong Wang; Yutao Du; Fan Li; Shiyang Chang; Yangchen Su; Aijing Liu; Min Shi (Pflügers Archiv - European Journal of Physiology, 2023)

First report of tea leaf spot disease caused by Bipolaris bicolor on tea plants (Camellia sinensis cv. Fenghuang Dancong) in China - Yu-Xian Zhong; Ying-Yao Liu; Min Li; Dylan O’Neill Rothenberg; Zhen Zeng; Ya-Hui Huang; Chang-Yu Yan (Journal of Plant Pathology, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Increased ascorbic acid synthesis by overexpression of AcGGP3 ameliorates copper toxicity in kiwifruit - Xiaoying Liu; Chang Cheng; Yan Min; Xiaodong Xie; Abu Naim Md. Muzahid; Haiyan Lv; Hua Tian; Congxiao Zhang; Can Ye; Shifeng Cao; Peng Chen; Caihong Zhong; et al. (Journal of Hazardous Materials, 2023)

An efficiency-driven approach for global ecological industrial parks - Shih-Fang Lo; Wen-Min Lu; Che-Wei Chang; Shiu-Wan Hung; Li-Ling Yang (Journal of Cleaner Production, 2023)

Geographic factors explain soil nitrogen and phosphorus stoichiometry in the Chinese wetlands - Yuhuan Chang; Fujing Wang; Mi Zhang; Derong Xiao; Wenjuan Han; Xiangyong Zheng; Min Zhao; Baoqiang Lv; Lihu Xiong; Hepeng Li; Zhao Huang; Huanyi Miao (CATENA, 2023)

Biodegradability enhancement of waste lubricating oil regeneration wastewater using electrocoagulation pretreatment - Li-li Shan; Zhao Tan; Yu Chen; Ruo-shan Wang; Meng Zhang; Chang-long Pang; Yu-Hong Cui; Zhi-min Liao; Hong-qiang Ma; Ze-bing Zhu (Environmental Science and Pollution Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Molecular characterization and expression of twenty interleukin-17 transcripts in the common Chinese cuttlefish (Sepiella japonica) in response to Vibrio harveyi infection - Xu Zhou; Pei-Xuan Fang; Hui-Min Cao; Jian-Jun Xie; Shuang Li; Chang-Feng Chi (Fish & Shellfish Immunology, 2023)

Effects of nitrogen forms on nitrogen utilization, yield, and quality of two wheat varieties with different gluten characteristics - Haixing Cui; Yongli Luo; Chunhui Li; Yonglan Chang; Min Jin; Yong Li; Zhenlin Wang (European Journal of Agronomy, 2023)

Novel double Z-scheme g-C3N5/BiFeO3/ZnIn2S4 heterojunction system with enhanced visible-light-induced photo-Fenton activity towards sulfamethoxazole degradation - Govindan Jagan; Karunamoorthy Saravanakumar; Jianbing Li; Yeomin Yoon; Chang Min Park (Chemical Engineering Journal, 2023)

Urbanization shifts long‐term phenology and severity of phytoplankton blooms in an urban lake through different pathways - Yuanrui Li; Juan Tao; Yunlin Zhang; Kun Shi; Junjun Chang; Min Pan; Lirong Song; Erik Jeppesen; Qichao Zhou (Global Change Biology, 2023)
Climate change can induce phytoplankton blooms (PBs) in eutrophic lakes worldwide, and these blooms severely threaten lake ecosystems and human health. However, it is unclear how urbanization and its interaction with climate impact PBs, which has implications for the management of lakes. Here, we used multi‐source remote sensing data and integrated the Virtual‐Baseline Floating macroAlgae Height (VB‐FAH) index and OTSU threshold automatic segmentation algorithm to extract the area of PBs in Lake Dianchi, China, which has been subjected to frequent PBs and rapid urbanization in its vicinity. We further explored long‐term (2000–2021) trends in the phenological and severity metrics of PBs and quantified the contributions from urbanization, climate change, and also nutrient levels to these trends. When comparing data from 2011–2021 to 2000–2010, we found significantly advanced initiation of PBs (28.6 days) and noticeably longer duration (51.9 days) but an insignificant trend in time of disappearance. The enhancement of algal nutrient use efficiency, likely induced by increased water temperature and reduced nutrient concentrations, presumably contributed to an earlier initiation and longer duration of PBs, while there was a negative correlation between spring wind speed and the initiation of PBs. Fortunately, we found that both the area of the PBs and the frequency of severe blooms (covering more than 19.8 km 2 ) demonstrated downward trends, which could be attributed to increased wind speed and/or reduced nutrient levels. Moreover, the enhanced land surface temperature caused by urbanization altered the thermodynamic characteristics between the land and the lake, which, in turn, possibly caused an increase in local wind speed and water temperature, suggesting that urbanization can differently regulate the phenology and severity of PBs. Our findings have significant implications for the understanding of the impacts of urbanization on PB dynamics and for improving lake management practices to promote sustainable urban development under global change.

Nitrogen deposition weakens the stimulatory effect of Moso bamboo (Phyllostachys edulis) leaf litter on soil CO2 emissions - Shoujia Zhuo; Youchao Chen; Haikuo Zhang; Wenting Jiang; Bo Fan; Yongfu Li; Bing Yu; Wenjun Li; Min Duan; Scott X. Chang; Yanjiang Cai (Journal of Soils and Sediments, 2023)

Benzo(a)pyrene regulates chaperone-mediated autophagy via heat shock protein 90 - Min Su; Shuhong Zhou; Jun Li; Nan Lin; Tao Chi; Mengdi Zhang; Xiaoli Lv; Yuxia Hu; Tuya Bai; Fuhou Chang (Toxicology Letters, 2023)

Mixed cropping increases grain yield and lodging resistance by improving the canopy light environment of wheat populations - Chunhui Li; Wenqian Li; Yongli Luo; Min Jin; Yonglan Chang; Haixing Cui; Shufang Sun; Yong Li; Zhenlin Wang (European Journal of Agronomy, 2023)

One global disseminated 193 kb high-risk hybrid plasmid harboring tet(X4), mcr or blaNDM threatening public health - Min Li; Haoran Zhang; Wengang Zhang; Ying Cao; Bingqing Sun; Qin Jiang; Yu Zhang; Haodong Liu; WenNan Guo; Cheng Chang; Nan Zhou; Chao Lv; et al. (Science of The Total Environment, 2023)

Electrocatalyst with fluorinated protective layer for efficient oxygen reduction in the operating temperature of PEMFCs - Chang Li; Wenlong Wang; Sheng Zhu; Hui Pan; Qunjie Xu; PengHui Shi; YuLin Min (Chemical Engineering Journal, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Biochar modification to enhance arsenic removal from water: a review - Luping Tian; Hao Li; Zhaofeng Chang; Ni Liang; Min Wu; Bo Pan (Environmental Geochemistry and Health, 2023)

Enhanced virulence of genetically engineered Autographa californica nucleopolyhedrovirus owing to accelerated viral DNA replication aided by inserted ascovirus genes - Huan Yu; Chang-Jin Yang; Yi-Yi Ou-Yang; Yue Tong; Hui-Yu Lan; Jia-Min Gan; Shi-Wei Li; Ding-Yi Bai; Guo-Hua Huang (Pesticide Biochemistry and Physiology, 2023)

Nitrogen regulates stem lodging resistance by breaking the balance of photosynthetic carbon allocation in wheat - Chunhui Li; Yonglan Chang; Yongli Luo; Wenqian Li; Min Jin; Yuanyuan Wang; Haixing Cui; Shufang Sun; Yong Li; Zhenlin Wang (Field Crops Research, 2023)

Polyoxometalate anchored zinc oxide nanocomposite as a highly effective photocatalyst and bactericide for wastewater decontamination - Cuili Xing; Min Ma; Jiangnan Chang; Zhe Ji; Peifang Wang; Lin Sun; Shijie Li; Mingxue Li (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Changes of dissolved organic matter fractions and formation of oxidation byproducts during electrochemical treatment of landfill leachates: Development of spectroscopic indicators for process optimization - Bi-Cun Jiang; Ye-Chao Tian; Ai-Min Li; Yu-Ze Han; Ze-Tao Wu; Chang Lu; Hai-Ou Song; Rong Ji; Wen-Tao Li; Gregory V. Korshin (Water Research, 2023)

Identification and characterization of two long-type peptidoglycan recognition proteins, PGRP-L1 and PGRP-L2, in the orange-spotted grouper, Epinephelus coioides - Jing Hou; Wei Hao; Min Chang Li; Zhen Gan; Shan Nan Chen; Yi Shan Lu; Li Qun Xia (Fish & Shellfish Immunology, 2023)

Novel umami peptide from Hypsizygus marmoreus hydrolysate and molecular docking to the taste receptor T1R1/T1R3 - Jincui Chang; Xue Li; Yi Liang; Tao Feng; Min Sun; Shiqing Song; Lingyun Yao; Huatian Wang; Feina Hou (Food Chemistry, 2023)

Regulation of Nitrogen Metabolism, Photosynthetic Activity, and Yield Attributes of Spring Wheat by Nitrogen Fertilizer in the Semi-arid Loess Plateau Region - Zechariah Effah; Lingling Li; Junhong Xie; Chang Liu; Aixia Xu; Benjamin Karikari; Sumera Anwar; Min Zeng (Journal of Plant Growth Regulation, 2023)

Catalytic hydroconversion of an organic waster oil to cyclanes over Ni/SiO2 - Li Li; Xian-Yong Wei; Chang-Wang Shao; Zhuang Li; Jia-Hao Li; Zi-Chun Fan; Kun-Lang Lu; Fang-Jing Liu; Qian-Qian Kong; Ji Zhao; Zhong-Qiu Liu; Zhi-Min Zong (Fuel, 2023)

Honeycomb-like N/O self-doped hierarchical porous carbons derived from low-rank coal and its derivatives for high-performance supercapacitor - Li Li; Xian-Yong Wei; Chang-Wang Shao; Fan Yin; Bing-Kang Sun; Fang-Jing Liu; Jia-Hao Li; Zhong-Qiu Liu; Zhi-Min Zong (Fuel, 2023)

Towards jet fuel from technical lignins: Feedstock-catalyst-product interactions revealed during catalytic hydrogenolysis - Matthew S. Kollman; Xiao Jiang; Runkun Sun; Xia Zhang; Wenzhi Li; Hou-min Chang; Hasan Jameel (Chemical Engineering Journal, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Precise orbit determination for the Haiyang-2D satellite using new onboard BDS-3 B1C/B2a signal measurements - Min Li; Renhai Mu; Kecai Jiang; Youcun Wang; Xuanxuan Zhang; Chuntao Chang; Qile Zhao (GPS Solutions, 2022)

Stochastic analysis of the variability of groundwater flow fields in heterogeneous confined aquifers of variable thickness - Ching-Min Chang; Chuen-Fa Ni; We-Ci Li; Chi-Ping Lin; I-Hsian Lee (Stochastic Environmental Research and Risk Assessment, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Ecophysiological Responses of Five Mangrove Species (Bruguiera gymnorrhiza, Rhizophora stylosa, Aegiceras corniculatum, Avicennia marina, and Kandelia obovata) to Chilling Stress - Shu-Min Wang; You-Shao Wang; Bo-Yu Su; Yue-Yue Zhou; Li-Fang Chang; Xiao-Yu Ma; Xiao-Mei Li (Frontiers in Marine Science, 2022)
Although the low temperature is a critical growth constraint on plants, the physiological mechanism remains unclear, especially in mangrove plants. Hence, the morphological characteristics of five mangrove plants ( Bruguiera gymnorrhiza , Rhizophora stylosa , Aegiceras corniculatum , Avicennia marina , and Kandelia obovata ) were compared under chilling stress. The contents of hydrogen peroxide (H 2 O 2 ), malondialdehyde (MDA), and proline were tested. Activities of reactive oxygen species (ROS)-scavenging enzyme [superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT)] were also measured after chilling stress. It was concluded that K. obovata can well tolerate chilling stress, and B. gymnorrhiza suffered the most severe chilling damage. Leaf-morphology observation exhibited that K. obovata and A. corniculatum can sustain chilling stress, while B. gymnorrhiza wilted and A. marina turned brown. The content of H 2 O 2 increased at first and subsequently decreased in all plants. MDA increased instantaneously in B. gymnorrhiza and R. stylosa but changed slowly in K. obovata and A. corniculatum . The high content of proline accumulated in B. gymnorrhiza and K. obovata . The activities of the SOD, POD, and CAT increased at first and then decreased in all mangrove species. The antioxidants maintained high activity in K. obovata while decreasing earliest in A. marina exposed to the long-term chilling stress. Principal component analysis (PCA) indicated that high antioxidant enzyme activities play key roles in chilling tolerance for mangrove plants. The longer-term chilling tolerance of K. obovata may be related to the high antioxidant enzyme activities and proline accumulation. Lower H 2 O 2 and MDA contents strengthen the anti-chilling ability of A. corniculatum. Further investigation on the molecular mechanisms will facilitate the understanding of the anti-chilling ability of mangrove plants.

Numerical investigation of the control factors driving Zhe-Min Coastal Current - Yang Zhang; Fei Chai; Joseph Zhang; Yang Ding; Min Bao; Yunwei Yan; Hong Li; Wei Yu; Liang Chang (Acta Oceanologica Sinica, 2022)

A quadruple recombination event discovered in hepatitis E virus - Hao Shen; Shuning Liu; Min Ding; Haixia Gu; Ming Chang; Yanshuang Li; Hua Wang; Xingwen Bai; Hongxing Shen (Archives of Virology, 2021)

Abnormal meiosis in fertile and sterile triploid cyprinid fish - Chun Zhang; Qi Li; La Zhu; Wangchao He; Conghui Yang; Hui Zhang; Yu Sun; Luojing Zhou; Yuandong Sun; Shurun Zhu; Chang Wu; Min Tao; et al. (Science China Life Sciences, 2021)

Extract of Polygala tenuifolia, Angelica tenuissima, and Dimocarpus longan Reduces Behavioral Defect and Enhances Autophagy in Experimental Models of Parkinson’s Disease - Huan Li; Joonki Kim; Huynh Nguyen Khanh Tran; Chang Hwan Lee; Jonghyun Hur; Min Cheol Kim; Hyun Ok Yang (NeuroMolecular Medicine, 2021)

A Survey on How Ocular Surface Demodex Infestation Interactively Associates with Diabetes Mellitus and Dry Eye Disease - Chang Huang; Shuze Chen; Sheng Fu; Yingli Li; Zhenhao Li; Siqi Li; Xiaoqian Liang; Zihong Wang; Zhoucheng Wang; Yifan Chen; Qixin Deng; Guoguo Yi; et al. (Acta Parasitologica, 2021)
Purpose Prevention of ocular surface (OS) Demodex infestation plays an important role in OS hygiene and variety of factors may be associated with it, in which diabetes mellitus (DM) or dry eye disease (DED) has caught the attention of most scholars. However, there has been no research on whether there was a potential interaction between DM and DED in the process of OS Demodex infestation. This cross-sectional study was implemented in Zhujiang Hospital of Southern Medical University. Methods Ophthalmologic interviews, questionnaires, and examinations were conducted. Factors including general information, DM status, dry eye condition, etc. were collected to study the correlation of DM and DED on OS Demodex infestation. Results After statistical analysis, we found that both DM ( P P = 0.013 R = 0.197, P R = 0.299, P P Conclusion This study provides a new evidence-based basis for clinical prevention and management of OS Demodex infestation.

Co-culture: stimulate the metabolic potential and explore the molecular diversity of natural products from microorganisms - Xiao-Yue Peng; Jin-Tao Wu; Chang-Lun Shao; Zhi-Yong Li; Min Chen; Chang-Yun Wang (Marine Life Science & Technology, 2021)

Alkalibacillus aidingensis sp. nov., an Bacterium Isolated from Aiding Lake in Xinjiang Province, North-West China - Rui Li; Li Yang; Rüdiger Pukall; Meina Neumann-Schaal; Chang-Gai Mu; Yong-Jiang Shi; Yun Wang; Gang-Qiang Jiang; Yu-Guang Zhou; Man Cai; Min Yin; Wen-Yong Zhu; et al. (Current Microbiology, 2021)

Oceanobacillus salinisoli sp. nov., a bacterium isolated from saline soil of Turpan city in Xinjiang province, north–west China - Wen-Yong Zhu; Li Yang; Zhou-Tian-Le Zhang; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Gang-Qiang Jiang; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2021)

Lake water storage change estimation and its linkage with terrestrial water storage change in the northeastern Tibetan Plateau - Ya-wei Li; Yu-zhe Wang; Min Xu; Shi-chang Kang (Journal of Mountain Science, 2021)

Exploring the Deeper Crustal Structure Beneath the Tatun Volcanic Area, Taiwan - Chien-Min Su; Wei-Jhe Wu; Strong Wen; Yi-Heng Li; Yen-Che Liao; Wen-Yen Chang; Chau-Huei Chen (Pure and Applied Geophysics, 2021)

Prenatal Stress Leads to the Altered Maturation of Corticostriatal Synaptic Plasticity and Related Behavioral Impairments Through Epigenetic Modifications of Dopamine D2 Receptor in Mice - Yingchun Li; Jing Rong; Haiquan Zhong; Min Liang; Chunting Zhu; Fei Chang; Rong Zhou (Molecular Neurobiology, 2021)

Long-term impact of accidental pollution on the distribution and risks of metals and metalloids in the sediment of the Longjiang River, China - Qian-Li Ma; Ling-Ai Yao; Qing-Wei Guo; Guang-Jie Zhou; Rong-Chang Liang; Qiao-Li Fang; Zhen-Cheng Xu; Xue-Min Zhao (Environmental Science and Pollution Research, 2021)

IL-33 deficiency protects mice from DSS-induced experimental colitis by suppressing ILC2 and Th17 cell responses - Xueying Qiu; Chang Qi; Xiaoxiao Li; Dai Fang; Min Fang (Inflammation Research, 2020)

Oceanobacillus halotolerans sp. nov., a bacterium isolated from salt lake in Xinjiang province, north-west China - Wen-Yong Zhu; Li Yang; Yong-Jiang Shi; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Perfusion Changes of Unexplained Early Neurological Deterioration After Reperfusion Therapy - Jingjing Fu; Ying Zhou; Qingqing Li; Genlong Zhong; Sheng Zhang; Ruiting Zhang; Chang Liu; Minming Zhang; Min Lou (Translational Stroke Research, 2020)

Paraherquamide J, a new prenylated indole alkaloid from the marine-derived fungus Penicillium janthinellum HK1-6 - Yao-Yao Zheng; Nan-Xing Shen; Zhao-Yang Liang; Li Shen; Min Chen; Chang-Yun Wang (Natural Product Research, 2020)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

African Orphan Crops Consortium (AOCC): status of developing genomic resources for African orphan crops - Prasad S. Hendre; Samuel Muthemba; Robert Kariba; Alice Muchugi; Yuan Fu; Yue Chang; Bo Song; Huan Liu; Min Liu; Xuezhu Liao; Sunil Kumar Sahu; Sibo Wang; et al. (Planta, 2019)

Identification of sugar response complex in the metallothionein OsMT2b gene promoter for enhancement of foreign protein production in transgenic rice - Chia-Yu Chang; Kuo-Wei Lee; Chung-Shen Wu; Yu-Hsing Huang; Ho-Chun Chang; Chien-Lung Chen; Chen-Tung Li; Min-Jeng Li; Chung-Fu Chang; Peng-Wen Chen (Plant Cell Reports, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic evolutionary analysis of soybean mosaic virus populations from three geographic locations in China based on the P1 and CP genes - Lei Zhang; Jing Shang; Qi Jia; Kai Li; Hui Yang; Huanhuan Liu; Zhongqin Tang; Xiaoli Chang; Min Zhang; Wenming Wang; Wenyu Yang (Archives of Virology, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Sequestration of Mn into the cell wall contributes to Mn tolerance in sugarcane (Saccharum officinarum L.) - Shu Yang; Ke Yi; Min Min Chang; Gui Zhi Ling; Zun Kang Zhao; Xiao Feng Li (Plant and Soil, 2019)

FcRγ deficiency improves survival in experimental sepsis by down-regulating TLR4 signaling pathway - Zhi-Min Wei; Zhuo Wang; Xiao-Jian Wan; Xian-Jing Li; Yi-Xing Li; Yang Bai; Xue Yang; Yong Yang; Shun-Chang Jiao; Zhe-Feng Liu (Immunologic Research, 2019)

Anti-diabetic vanadyl complexes reduced Alzheimer’s disease pathology independent of amyloid plaque deposition - Yaqiong Dong; Tessandra Stewart; Yue Zhang; Min Shi; Chang Tan; Xue Li; Lan Yuan; Aanchal Mehrotra; Jing Zhang; Xiaoda Yang (Science China Life Sciences, 2019)

CD8+ T cell/IL-33/ILC2 axis exacerbates the liver injury in Con A-induced hepatitis in T cell-transferred Rag2-deficient mice - Yuanyue Zhang; Chang Qi; Lingyun Li; Shuyao Hua; Fang Zheng; Feili Gong; Min Fang (Inflammation Research, 2019)

Higher Dietary Arachidonic Acid Levels Improved the Growth Performance, Gonad Development, Nutritional Value, and Antioxidant Enzyme Activities of Adult Sea Urchin (Strongylocentrotus intermedius) - Rantao Zuo; Min Li; Jun Ding; Yaqing Chang (Journal of Ocean University of China, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Improved plane layout of stabilizing piles based on the piecewise function expression of the irregular driving force - Wen-qiang Liu; Qun Li; Jian Lu; Chang-dong Li; Wen-min Yao; Jiang-bo Zeng (Journal of Mountain Science, 2018)

Mapping and comparative proteomic analysis of the starch biosynthetic pathway in rice by 2D PAGE/MS - Tao-Shan Chang; Chih-Wei Liu; Yu-Ling Lin; Chao-Yi Li; Arthur Z. Wang; Min-Wei Chien; Chang-Sheng Wang; Chien-Chen Lai (Plant Molecular Biology, 2017)

Three-dimensional arbitrarily anisotropic modeling for time-domain airborne electromagnetic surveys - Wei Huang; Fang Ben; Chang-Chun Yin; Qing-Min Meng; Wen-Jie Li; Gui-Xiang Liao; Shan Wu; Yong-Zai Xi (Applied Geophysics, 2017)

Effect of compatible herbs on the pharmacokinetics of effective components of Panax notoginseng in Fufang Xueshuantong Capsule - Huan-huan Pang; Meng-yi Li; Yuan Wang; Min-ke Tang; Chang-hua Ma; Jian-mei Huang (Journal of Zhejiang University-SCIENCE B, 2017)

High genetic diversity and absence of phylogeographic structure in breeding populations of vulnerable Saundersilarus saundersi (Charadriiformes: Laridae) in Bohai Bay, China - Ya-Nan Zhang; Bo-Ye Liu; Lu Dong; Hong-Xing Jiang; Xuan Wang; Xue-Min Wang; Chang-Zhan Song; Xiu-Ming Li; Shu-Hong Li (Conservation Genetics, 2017)

Evaluation of serum immunoglobulins concentrations and distributions in vitiligo patients - Yulong Li; Min Yang; Rui Zhang; Wan Liu; Kuo Zhang; Wei Wen; Lang Yi; Qiaoxian Wang; Mingju Hao; Hui Yang; Jianmin Chang; Jinming Li (Immunologic Research, 2016)

Phospholipase C Beta 1: a Candidate Signature Gene for Proneural Subtype High-Grade Glioma - Guangrong Lu; Jeffrey T. Chang; Zheyu Liu; Yong Chen; Min Li; Jay-Jiguang Zhu (Molecular Neurobiology, 2016)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

Streptomyces zhihengii sp. nov., isolated from rhizospheric soil of Psammosilene tunicoides - Mei-Juan Huang; Jing-Jing Fei; Nimaichand Salam; Chang-Jin Kim; Wael N. Hozzein; Min Xiao; Hai-Quan Huang; Wen-Jun Li (Archives of Microbiology, 2016)

Erratum to: Abyssicoccus albus gen. nov., sp. nov., a novel member of the family Staphylococcaceae isolated from marine sediment of the Indian Ocean - Zhao Jiang; Chang-Guo Yuan; Min Xiao; Xin-Peng Tian; Inam-Ullah Khan; Chang-Jin Kim; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2016)

Abyssicoccus albus gen. nov., sp. nov., a novel member of the family Staphylococcaceae isolated from marine sediment of the Indian Ocean - Zhao Jiang; Chang-Guo Yuan; Min Xiao; Xin-Peng Tian; Inam-Ullah Khan; Chang-Jin Kim; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2016)

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice - Pan Xu; Shu-ping Xu; Ke-zhu Wang; Cong Lu; Hong-xia Zhang; Rui-le Pan; Chang Qi; Yan-yan Yang; Ying-hui Li; Xin-min Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Cytotoxic 19-oxygenated steroids from the South China Sea gorgonian, Pacifigorgia senta - Min Chen; Lei Han; Xiu-Li Zhang; Chang-Yun Wang (Natural Product Research, 2016)

Human cytomegalovirus UL49 encodes an early, virion-associated protein essential for virus growth in human foreskin fibroblasts - Feng Zhu; Jian Yuan; Hong-Jian Li; Zhi-Feng Zeng; Zhi-Wen Luo; Shi-Qian Li; Chi-Qiang He; Xue-Fang Jia; Xin Zhang; Hui Zuo; Yi-Min Liu; Martin Chang; et al. (Archives of Virology, 2016)

Zebrafish Embryo Toxicity Microscale Model for Ichthyotoxicity Evaluation of Marine Natural Products - Hong Bai; Wen-Wen Kong; Chang-Lun Shao; Yun Li; Yun-Zhang Liu; Min Liu; Fei-Fei Guan; Chang-Yun Wang (Marine Biotechnology, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Infection Process and Pathogenic Mechanism of Phomopsis asparagi, the Asparagus Stem Blight Pathogen - Ying-Qing Yang; Bo Lan; Yan-Li Jian; Dong-Dong Chang; Shun-Liang Zhang; Xiang-Min Li (Phytoparasitica, 2016)

Canonical and non-canonical Wnt signaling control the regeneration of amputated rodent vibrissae follicles - Yan-Ping Yuan; Keng Huang; Yan-Min Xu; Xian-Cai Chen; Hai-Hong Li; Bo-Zhi Cai; Yang Liu; Huan Zhang; Yu Li; Chang-Min Lin (Journal of Molecular Histology, 2016)

Kocuria subflava sp. nov., isolated from marine sediment from the Indian Ocean - Zhao Jiang; Wei-Hua Zhang; Chang-Guo Yuan; Jia-Yang Chen; Li-Xiang Cao; Dong-Jin Park; Min Xiao; Chang-Jin Kim; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Comparative Analysis of Sporulating and Spore-Deficient Strains of Agrocybe salicacola Based on the Transcriptome Sequences - Wei-Min Chen; Xiao-Lei Zhang; Hong-Mei Chai; Li-Jiao Chen; Wu-Long Liu; Yong-Chang Zhao (Current Microbiology, 2015)

Actinomadura amylolytica sp. nov. and Actinomadura cellulosilytica sp. nov., isolated from geothermally heated soil - Jian-Yu Jiao; Lan Liu; En-Min Zhou; Da-Qiao Wei; Hong Ming; Wen-Dong Xian; Chang-Guo Yuan; Jing-Mei Zhong; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Expression of Wnt/β-catenin signaling, stem-cell markers and proliferating cell markers in rat whisker hair follicles - Chang-min Lin; Yan-ping Yuan; Xian-cai Chen; Hai-hong Li; Bo-zhi Cai; Yang Liu; Huan Zhang; Yu Li; Keng Huang (Journal of Molecular Histology, 2015)

Prevalence, quantification, and typing of human adenoviruses detected in river water in Taiwan - Zhon-Min Huang; Bing-Mu Hsu; Po-Min Kao; Tien-Yu Chang; Tsui-Kang Hsu; Ying-Ning Ho; Yi-Chun Yang; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Intranasal administration with recombinant Lactococcus lactis expressing heme oxygenase-1 reduces hyperoxia-induced lung inflammation in rat pups - Chang-Yi Wu; Luis G. Bermúdez-Humarán; Feng Yue; Min Li; Li-Ping Zhang (Biotechnology Letters, 2015)

Clinical Analysis of Internal Fixation Treatment of Intra-articular Calcaneal Fractures with Titanium Plate - Xiao-dong Chen; Chang-chun Zhang; Zhao-cheng Li; Heng Zhang; Xin-she Zhou; Min Deng (Cell Biochemistry and Biophysics, 2015)

Seasonal variation of Legionella in Taiwan’s reservoir and its relationships with environmental factors - Po-Min Kao; Bing-Mu Hsu; Tien-Yu Chang; Tsui-Kang Hsu; Kai-Jiun Tzeng; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Seasonal distribution of potentially pathogenic Acanthamoeba species from drinking water reservoirs in Taiwan - Po-Min Kao; Bing-Mu Hsu; Tsui-Kang Hsu; Jorn-Hon Liu; Hsiang-Yu Chang; Wen-Tsai Ji; Kai-Jiun Tzeng; Shih-Wei Huang; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Lentivirus-mediated Wnt10b overexpression enhances fracture healing in a rat atrophic non-union model - Feng Gao; Chang-qing Zhang; Yi-min Chai; Xiao-lin Li (Biotechnology Letters, 2015)

Streptomyces canchipurensis sp. nov., isolated from a limestone habitat - Wen-Jun Li; Salam Nimaichand; Zhao Jiang; Min-Jiao Liu; Thi-Nhan Khieu; Chang-Jin Kim; Wael N. Hozzein; Dong-Jin Park; Mohammed A. M. Wadaan; Debananda S. Ningthoujam (Antonie van Leeuwenhoek, 2014)

Some selected heavy metal concentrations in water, sediment, and oysters in the Er-Ren estuary, Taiwan: chemical fractions and the implications for biomonitoring - Yueh-Min Chen; Hong-Chun Li; Tsung-Ming Tsao; Liaug-Chi Wang; Yin Chang (Environmental Monitoring and Assessment, 2014)

Using hourly measurements to explore the role of secondary inorganic aerosol in PM2.5 during haze and fog in Hangzhou, China - Roeland Cornelis Jansen; Yang Shi; Jianmin Chen; YunJie Hu; Chang Xu; Shengmao Hong; Jiao Li; Min Zhang (Advances in Atmospheric Sciences, 2014)

Piromelatine exerts antinociceptive effect via melatonin, opioid, and 5HT1A receptors and hypnotic effect via melatonin receptors in a mouse model of neuropathic pain - Yuan-Yuan Liu; Dou Yin; Li Chen; Wei-Min Qu; Chang-Rui Chen; Moshe Laudon; Neng-Neng Cheng; Yoshihiro Urade; Zhi-Li Huang (Psychopharmacology, 2014)

Gene Expressing Difference in Sclerotial Formation of Morchella conica - Li-Jiao Chen; Hong-Mei Chai; Wei-Min Chen; Xing-Qi Huang; Yong-Chang Zhao (Indian Journal of Microbiology, 2014)

Characteristics of Malignant Tumors in 230 Husband–Wife Pairs - Ju Liu; Zhijian Xu; Kai Zhang; Huai Li; Sheng Chang; Xiaofeng Bi; Min Dai (Cell Biochemistry and Biophysics, 2014)

A new sesquiterpene from the Hainan gorgonian Menella kanisa Grassoff - Min Chen; Lei Han; Yu Wang; Xiu-Li Zhang; Chang-Yun Wang (Natural Product Research, 2014)

Ichnofabrics and their environmental interpretation from the fluvial deposits of the Middle Triassic Youfangzhuang Formation in Western Henan, Central China - Min Wang; Yongan Qi; Da Li; Mingyue Dai; Yuguang Chang (Journal of Earth Science, 2014)

Phenotypic characterization of C57BL/6J mice carrying the Disc1 gene from the 129S6/SvEv strain - Liang-Wen Juan; Chun-Chieh Liao; Wen-Sung Lai; Chia-Yuan Chang; Ju-Chun Pei; Wan-Rong Wong; Chih-Min Liu; Hai-Gwo Hwu; Li-Jen Lee (Brain Structure and Function, 2014)

The promoter and the 5′-untranslated region of rice metallothionein OsMT2b gene are capable of directing high-level gene expression in germinated rice embryos - Chung-Shen Wu; Dai-Yin Chen; Chung-Fu Chang; Min-Jeng Li; Kuei-Yu Hung; Liang-Jwu Chen; Peng-Wen Chen (Plant Cell Reports, 2014)

An Endophytic Sanguinarine-Producing Fungus from Macleaya cordata, Fusarium proliferatum BLH51 - Xue-Jun Wang; Chang-Li Min; Mei Ge; Rui-Hua Zuo (Current Microbiology, 2014)

The Role of Pentacyclic Triterpenoids in the Allelopathic Effects of Alstonia scholaris - Chao-Min Wang; Hsiao-Ting Chen; Tsai-Chi Li; Jen-Hsien Weng; Yun-Lian Jhan; Shi-Xun Lin; Chang-Hung Chou (Journal of Chemical Ecology, 2014)

Antidepressant-like effects and memory enhancement of a herbal formula in mice exposed to chronic mild stress - Xiu-Ping Sun; Si-Di Li; Zhe Shi; Teng-Fei Li; Rui-Le Pan; Qi Chang; Chuan Qin; Xin-Min Liu (Neuroscience Bulletin, 2013)

Pseudomonas oryzae sp. nov. isolated from a paddy soil in South China - Zhen Yu; Ming Chang; Min Wu; Guiqin Yang; Shungui Zhou; Li Zhuang (Archives of Microbiology, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

Uptake of arsenic species by turnip ( Brassica rapa L.) and lettuce ( Lactuca sativa L.) treated with roxarsone and its metabolites in chicken manure - Lian Xi Huang; Li Xian Yao; Zhao Huan He; Chang Min Zhou; Guo Liang Li; Bao Mei Yang; Ying Fen Li (Food Additives & Contaminants: Part A, 2013)

ADAM17 mediates hypoxia-induced drug resistance in hepatocellular carcinoma cells through activation of EGFR/PI3K/Akt pathway - Xiang-jun Wang; Chang-wei Feng; Min Li (Molecular and Cellular Biochemistry, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Acid loading stimulates rat glomerular mesangial cells proliferation through Na+–H+ exchanger isoform 1 (NHE1)-dependent pathway - Kun Li; Wei Su; Man Li; Chang-jie Chen; Yong-yu Li; Lin-yun Lai; Ming-min Zhang; Shao-jun Liu; Jakub Fichna; Ai Peng; Chuan-ming Hao; Yong Gu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Identification of two SCAR markers co-segregated with the dominant Ms and recessive ms alleles in onion (Allium cepa L.) - Yan Yan Yang; Yu Meng Huo; Jun Miao; Bing Jiang Liu; Su Ping Kong; Li Min Gao; Chang Liu; Zhen Bao Wang; Yasuki Tahara; Hidemi Kitano; Xiong Wu (Euphytica, 2013)

Perifosine Induces Cell Apoptosis in Human Osteosarcoma Cells: New Implication for Osteosarcoma Therapy? - Chen Yao; Jian-jun Wei; Zu-yu Wang; Hui-min ding; Dong Li; Shi-chang Yan; Yong-jiang Yang; Zhang-ping Gu (Cell Biochemistry and Biophysics, 2013)

Subtype of dietary fat in relation to risk of Hodgkin lymphoma: a population-based case–control study in Connecticut and Massachusetts - Yongshun Gao; Qian Li; Bryan A. Bassig; Ellen T. Chang; Min Dai; Qin Qin; Yawei Zhang; Tongzhang Zheng (Cancer Causes & Control, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

VSL#3 probiotics exerts the anti-inflammatory activity via PI3k/Akt and NF-κB pathway in rat model of DSS-induced colitis - Cong Dai; Chang-Qing Zheng; Fan-ji Meng; Zheng Zhou; Li-xuan Sang; Min Jiang (Molecular and Cellular Biochemistry, 2013)

Body size and risk of Hodgkin’s lymphoma by age and gender: a population-based case–control study in Connecticut and Massachusetts - Qian Li; Ellen T. Chang; Bryan A. Bassig; Min Dai; Qin Qin; Yongshun Gao; Yawei Zhang; Tongzhang Zheng (Cancer Causes & Control, 2013)

The variation of tree beta diversity across a global network of forest plots - Miquel De Cáceres; Pierre Legendre; Renato Valencia; Min Cao; Li‐Wan Chang; George Chuyong; Richard Condit; Zhanqing Hao; Chang‐Fu Hsieh; Stephen Hubbell; David Kenfack; Keping Ma; et al. (Global Ecology and Biogeography, 2012)
Aims With the aim of understanding why some of the world's forests exhibit higher tree beta diversity values than others, we asked: (1) what is the contribution of environmentally related variation versus pure spatial and local stochastic variation to tree beta diversity assessed at the forest plot scale; (2) at what resolution are these beta‐diversity components more apparent; and (3) what determines the variation in tree beta diversity observed across regions/continents? Location World‐wide. Methods We compiled an unprecedented data set of 10 large‐scale stem‐mapping forest plots differing in latitude, tree species richness and topographic variability. We assessed the tree beta diversity found within each forest plot separately. The non‐directional variation in tree species composition among cells of the plot was our measure of beta diversity. We compared the beta diversity of each plot with the value expected under a null model. We also apportioned the beta diversity into four components: pure topographic, spatially structured topographic, pure spatial and unexplained. We used linear mixed models to interpret the variation of beta diversity values across the plots. Results Total tree beta diversity within a forest plot decreased with increasing cell size, and increased with tree species richness and the amount of topographic variability of the plot. The topography‐related component of beta diversity was correlated with the amount of topographic variability but was unrelated to its species richness. The unexplained variation was correlated with the beta diversity expected under the null model and with species richness. Main conclusions Because different components of beta diversity have different determinants, comparisons of tree beta diversity across regions should quantify not only overall variation in species composition but also its components. Global‐scale patterns in tree beta diversity are largely coupled with changes in gamma richness due to the relationship between the latter and the variation generated by local stochastic assembly processes.

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

The effects assessment of firm environmental strategy and customer environmental conscious on green product development - Ming-Tien Tsai; Li-Min Chuang; Shu-Tsung Chao; Hsiao-Ping Chang (Environmental Monitoring and Assessment, 2012)

The Zanthoxylum schinifolium seed oil modulates immune function under the biological safety level - Joung-Wook Seo; Dae-Hun Park; Yong-Chun Li; Hur-Je Kang; Hong De Xu; Young-Jin Kim; Jong-Hwa Lee; Myung-Sup Lee; In Chul Lee; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; et al. (Molecular & Cellular Toxicology, 2012)

Distribution and linkage disequilibrium analysis of polymorphisms of MC4R, LEP, H-FABP genes in the different populations of pigs, associated with economic traits in DIV2 line - Zhe Chao; Feng Wang; Chang-Yan Deng; Li-Min Wei; Rui-Ping Sun; Hai-Long Liu; Quan-Wei Liu; Xin-Li Zheng (Molecular Biology Reports, 2012)

Catalytic characteristics of plant-esterase from wheat flour - Chang-jun Hou; Kun He; Li-min Yang; Dan-qun Huo; Mei Yang; Shun Huang; Liang Zhang; Cai-hong Shen (World Journal of Microbiology and Biotechnology, 2012)

Biological safety and B cells activation effects of Zanthoxylum schinifolium - Dae-Hun Park; Yong-Il Park; Yong-Chun Li; Hong De Xu; Jong-Hwa Lee; Young-Jin Kim; Soon-Ae Jang; Sung Jin Park; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; Min-Jae Lee (Molecular & Cellular Toxicology, 2011)

Crop nitrogen use and soil mineral nitrogen accumulation under different crop combinations and patterns of strip intercropping in northwest China - Chun-Jie Li; Yu-Ying Li; Chang-Bing Yu; Jian-Hao Sun; Peter Christie; Min An; Fu-Suo Zhang; Long Li (Plant and Soil, 2011)

Development and application of RAPD-SCAR markers to identify intra-species hybrids of industrial Saccharomyces cerevisiae - Pin-Mei Wang; Xue-Chang Wu; Xiao-Qin Chi; Yu-Dong Li; Dao-Qiong Zheng; Rui Ding; Hang Min (World Journal of Microbiology and Biotechnology, 2011)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.

Identification of an aminopeptidase from the skeletal muscle of grass carp (Ctenopharyngodon idellus) - Li-Gen Zhou; Bing-Xin Liu; Le-Chang Sun; Kenji Hara; Wen-Jin Su; Min-Jie Cao (Fish Physiology and Biochemistry, 2010)

Primary scientific results of Chang’E-1 lunar mission - ZiYuan Ouyang; ChunLai Li; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; JianJun Liu; Wei Zuo; Yan Su; WeiBin Wen; Wei Bian; BaoChang Zhao; et al. (Science China Earth Sciences, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Triaxial ellipsoid models of the Moon based on the laser altimetry data of Chang’E-1 - WenRui Wang; Fei Li; JianJun Liu; Xin Ren; XiaoDuan Zou; LingLi Mu; JianGuo Yan; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

17β-Estradiol inhibits prostaglandin E2-induced COX-2 expressions and cell migration by suppressing Akt and ERK1/2 signaling pathways in human LoVo colon cancer cells - Tung-Yuan Lai; Li-Mien Chen; Jing-Ying Lin; Bor-Show Tzang; James A. Lin; Chang-Hai Tsai; Yueh-Min Lin; Chih-Yang Huang; Chung-Jung Liu; Hsi-Hsien Hsu (Molecular and Cellular Biochemistry, 2010)

The global image of the Moon obtained by the Chang’E-1: Data processing and lunar cartography - ChunLai Li; JianJun Liu; Xin Ren; LingLi Mou; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; Yan Su; WeiBin Wen; Wei Bian; et al. (Science China Earth Sciences, 2010)

Epidemic risk analysis after the Wenchuan Earthquake using remote sensing - Chunxiang Cao; Chaoyi Chang; Min Xu; Jian Zhao; Mengxu Gao; Hao Zhang; Jianping Guo; Jianghong Guo; Lei Dong; Qisheng He; Linyan Bai; Yunfei Bao; et al. (International Journal of Remote Sensing, 2010)

Change detection of an earthquake-induced barrier lake based on remote sensing image classification - Min Xu; Chunxiang Cao; Hao Zhang; Jianping Guo; Kaneyuki Nakane; Qisheng He; Jianghong Guo; Chaoyi Chang; Yunfei Bao; Mengxu Gao; Xiaowen Li (International Journal of Remote Sensing, 2010)

The interaction between interferon-induced protein with tetratricopeptide repeats-1 and eukaryotic elongation factor-1A - Hong-Tao Li; Yong-Ping Su; Tian-Min Cheng; Jian-Ming Xu; Jie Liao; Ji-Chuan Chen; Chang-You Ji; Guo-Ping Ai; Jun-Ping Wang (Molecular and Cellular Biochemistry, 2010)

Viral infection of tobacco plants improves performance of Bemisia tabaci but more so for an invasive than for an indigenous biotype of the whitefly - Jian Liu; Meng Li; Jun-min Li; Chang-jun Huang; Xue-ping Zhou; Fang-cheng Xu; Shu-sheng Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Valve movement response of the freshwater clam Corbicula fluminea following exposure to waterborne arsenic - Chung-Min Liao; Sheng-Feng Jau; Chieh-Ming Lin; Li-John Jou; Chen-Wuing Liu; Vivian Hsiu-Chuan Liao; Fi-John Chang (Ecotoxicology, 2009)

Respiratory face mask: a novel and cost-effective device for use during the application of myocardial ischemia in rats - Yuan Yuan; Fei Li; Yue-min Wang; Rong-qing Zhang; Li-ping Wei; Hai-chang Wang (Journal of Zhejiang University-SCIENCE B, 2009)

Localization and characterization of VVA0331, a 489-kDa RTX-like protein, in Vibrio vulnificus YJ016 - Li-Fang Chou; Hwei-Ling Peng; Yu-Chung Yang; Min-Chieh Kuo; Hwan-You Chang (Archives of Microbiology, 2009)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Genetic structure and diversity of cultivated soybean (Glycine max (L.) Merr.) landraces in China - Yinghui Li; Rongxia Guan; Zhangxiong Liu; Yansong Ma; Lixia Wang; Linhai Li; Fanyun Lin; Weijiang Luan; Pengyin Chen; Zhe Yan; Yuan Guan; Li Zhu; et al. (Theoretical and Applied Genetics, 2008)

Evolution of Exceptionally Large Genes in Prokaryotes - Min-Chieh Kuo; Li-Fang Chou; Hwan-You Chang (Journal of Molecular Evolution, 2008)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Isolation of a human gallbladder cancer cell clone with high invasive phenotype in vitro and metastatic potential in orthotopic model and inhibition of its invasiveness by heparanase antisense oligodeoxynucleotides - Xin-Zhong Chang; Zhan-Min Wang; Jin-Ming Yu; Fu-Guo Tian; Wei Jin; Yi Zhang; Jie Yu; Lian-Fang Li; Xiao-Feng Liu; Zhi-Wei Li; Zhi-Min Shao (Clinical & Experimental Metastasis, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Determination of Trace Mercury by Solid Substrate-Room Temperature Phosphorimetry Quenching Method Based on Catalytic Effect of Hg2+on Formation of the Ion Association Complex [Sn(XO)6]4+·[(Fin)4] - Jia-Ming Liu; Ruo-Hong Wu; De-Chang Li; Ping Zhou; Min-Min Zheng; Xiao-Yi Zeng; Dong-Xia Liu; Xiao-Mei Huang; Guo-Hui Zhu (Journal of Fluorescence, 2006)

In-situ nitrogen removal from the eutrophic water by microbial-plant integrated system - Hui-qing Chang; Xiao-e Yang; Yun-ying Fang; Pei-min Pu; Zheng-kui Li; Zed Rengel (Journal of Zhejiang University-SCIENCE B, 2006)

Mutant of a Xylanase-producing Strain of Aspergillus niger in Solid State Fermentation by Low Energy Ion Implantation - Min Wu; Shi Chang Li; Jian Ming Yao; Ren Rui Pan; Zeng Liang Yu (World Journal of Microbiology and Biotechnology, 2005)

Direct effects of 9-anthracene compounds on cystic fibrosis transmembrane conductance regulator gating - Tomohiko Ai; Silvia G. Bompadre; Yoshiro Sohma; Xiaohui Wang; Min Li; Tzyh-Chang Hwang (Pflügers Archiv - European Journal of Physiology, 2004)

Floral development of Kingdonia (Ranunculaceae s. l., Ranunculales) - Yi Ren; Zhi-jun Li; Hong-li Chang; Yong-ji Lei; An-min Lu (Plant Systematics and Evolution, 2004)

Intracellular expression of Vitreoscilla hemoglobin in Aspergillus terreus to alleviate the effect of a short break in aeration during culture - Yu-Hui Lin; Ywan-Feng Li; Min-Chang Huang; Ying-Chieh Tsai (Biotechnology Letters, 2004)

Climatic Aridity and the Relocations of the Zhou Culture in the Southern Loess Plateau of China - Chun Chang Huang; Shichao Zhao; Jiangli Pang; Qunying Zhou; Shue Chen; Pinghua Li; Longjiang Mao; Min Ding (Climatic Change, 2003)

(R)-Oxynitrilase-catalysed synthesis of chiral silicon-containing aliphatic (R)-ketone-cyanohydrins - Ning Li; Min-Hua Zong; Chen Liu; Hua-Song Peng; Hua-Chang Wu (Biotechnology Letters, 2003)

Is Large Body Size always Advantageous for Terrestrial Adaptation? - Min-Li Tsai; Jan-Jung Li; Chang-Feng Dai (Evolutionary Ecology, 2000)

Monoclonal anti-androgen receptor antibodies: Production, characterization, and potential diagnostic applications - Charles C.-Y. Smith; Win-Jing Young; Chi-Huei Wang; Li-Ping Jin; Xiang-Dong Ji; Qi Guan; Min Wang; Chawnshang Chang (Molecular and Cellular Biochemistry, 1999)

Why selection favors protandrous sex change for the parasitic isopod, Ichthyoxenus fushanensis (Isopoda: Cymothoidae) - Min-Li Tsai; Jan-Jung Li; Chang-Feng Dai (Evolutionary Ecology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)